Zona Franca De Manaus: Compliance como instrumento de preservação ambiental - Carvalho, Denise Beatriz Magalhães de Figueiredo (2024)
This research deals with the Manaus Free Trade Zone, addressing its historical origin, its regulatory frameworks and its general impacts on the region, with special attention to the environmental impact. In this sense, an approach to environmental compliance is made in the context of the Manaus Free Trade Zone, providing a brief overview of its origin, its guiding aspects, its interconnection with policies related to the environment and analyzing compliance as an effective instrument for environmental preservation. from a legal perspective. This study also seeks to bring the relationship between the Courts of Auditors and compliance with a focus on the regulatory and supervisory role of the institution for compliance with this instrument, also presenting the report of the Federal Court of Auditors in relation to the public policy of the Manaus Free Trade Zone.